Evaluating integrin activation with time-resolved flow cytometry - Sambrano, Jesus (J Biomed Opt, 2018)
Förster resonance energy transfer (FRET) continues to be a useful tool to study movement and interaction between proteins within living cells. When FRET as an optical technique is measured with flow cytometry, conformational changes of proteins can be rapidly measured cell-by-cell for the benefit of screening and profiling. We exploit FRET to study the extent of activation of [Formula: see text] integrin dimers expressed on the surface of leukocytes. The stalk-like transmembrane heterodimers when not active lay bent and upon activation extend outward. Integrin extension is determined by changes in the distance of closest approach between an FRET donor and acceptor, bound at the integrin head and cell membrane, respectively. Time-resolved flow cytometry analysis revealed donor emission increases up to 17%, fluorescence lifetime shifts over 1.0 ns during activation, and FRET efficiencies of 37% and 26% corresponding to the inactive and active integrin state, respectively. Last, a graphical phasor analysis, including population clustering, gating, and formation of an FRET trajectory, added precision to a comparative analysis of populations undergoing FRET, partial donor recovery, and complete donor recovery. This work establishes a quantitative cytometric approach for profiling fluorescence donor decay kinetics during integrin conformational changes on a single-cell level.